Artificial Intelligence and the Identity of the Researcher - Paula Chimenti (RAC: Revista de Administração Contemporânea)
The development and large-scale dissemination of generative artificial intelligence (GAI) – understood as technology capable of producing content similar to that created by humans – raises questions about the future of many sectors, including education. The debate around the future of research and researchers has intensified. Will we be replaced? Will we become obsolete in less than a decade?